Theory and practice. Verifying the command skills of the graduates of Polish Military School in Genoa and Cuneo (1861-1862) during the January Uprising (1863-1864) - Buława, Adam (Saeculum Christianum. Pismo Historyczne, 2021)
In the run-up to independence uprising, from October 1861 to June 1862 thanks to permit the authorities of the United Kingdom of Italy and the intervention of Giuseppe Garibaldi functioned in Genoa and Cuneo Polish Military School was closed due to diplomatic pressure by the partitioning powers. Over the course of several months was the theoretical preparation of the January Uprising leadership cadre, and 15 graduates covered the self-command of the guerrilla armed parties. 4 of them belonged to the most prominent commanders for the entire war, also 4 can be regarded as promising. One showed just to be average, two were clearly weak. In two cases, it is difficult to set a clear assessment. For two commanders, former soldiers of the Austrian army were disappointing in the field. The Italic episode was an added element of military knowledge. The most significant was the individual’s charac-teristics, although it certainly proved to be a useful body of knowledge transmitted by the emigration of well-prepared teachers cadet school.